2017
DOI: 10.1093/mnras/stx3008
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of non-spherical dust in the coma of 67P/Churyumov– Gerasimenko constrained by GIADA and ROSINA data

Abstract: Among the comet 67P/Churyumov-Gerasimenko (67P/C-G) in situ measurements, the closest that have ever been performed at a comet nucleus, are also those of speed, mass, and crosssection of cometary grains performed by the Grain Impact Analyser and Dust Accumulator (GIADA) instrument. To interpret GIADA data, we performed dust dynamical numerical simulations with both spherical and non-spherical (spheroids) shapes. This allowed us to analyse how the grain non-sphericity affects the data interpretation. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…We here consider chunks shaped as oblate ellipsoids with axis ratio 4, exposing their largest cross section to the gas flow at =0 h ( 2.5 times that of an equal-mass sphere), that turn with constant radial velocity to expose their smallest cross section ( 0.63 times that of an equal-mass sphere) during the first 500 m of flight. The chunk shape is close to the axis ratio of 5 needed in order to match the particle speeds measured by Rosetta/GIADA according to Ivanovski et al (2017a). The time needed for the chunks to reach the height of 500 m is similar to that needed by the aerodynamic torque to set non-spherical chunks in rotation according to simulations by Ivanovski et al (2017b).…”
Section: Dust Ejectionsupporting
confidence: 53%
“…We here consider chunks shaped as oblate ellipsoids with axis ratio 4, exposing their largest cross section to the gas flow at =0 h ( 2.5 times that of an equal-mass sphere), that turn with constant radial velocity to expose their smallest cross section ( 0.63 times that of an equal-mass sphere) during the first 500 m of flight. The chunk shape is close to the axis ratio of 5 needed in order to match the particle speeds measured by Rosetta/GIADA according to Ivanovski et al (2017a). The time needed for the chunks to reach the height of 500 m is similar to that needed by the aerodynamic torque to set non-spherical chunks in rotation according to simulations by Ivanovski et al (2017b).…”
Section: Dust Ejectionsupporting
confidence: 53%
“…The first set includes the physical properties of the simulated particles. We considered homogeneous, isothermal spheres, oblate and prolate spheroids with aspect ratio a/b = 0.2 and 5.0, elongation values able to reproduce GIADA data (Ivanovski et al 2017b). We considered the dust physical properties retrieved by the GIADA measurements of 2015 August outbursts, i.e.…”
Section: Model Setup and Calibration With Giada Datamentioning
confidence: 99%
“… 2015 ) that have oblate or prolate shapes will also affect the dynamics as studied by Ivanovski et al. ( 2017a , b ). These latter authors have shown that not only may non-spherical particles begin to rotate in the gas flow but they may also accelerate to higher speeds than spherical ones.…”
Section: The Physics Of Developing Cometary Comaementioning
confidence: 95%